The Utilization of Digital Technologies in Learning Speaking Skills: Students’ Problems and Strategies at Islamic School - Kameswara, Putri Andini; Nashruddin, Wakhid; Priajana, Nana (PANYONARA: Journal of English Education, 2023)
Effective communication through speaking is a crucial element in today's globalized world. As technology continues to advance, it is essential to incorporate digital tools to enhance and teach speaking skills. An analysis was conducted to investigate the challenges encountered by students while learning English speaking skills through the utilization of digital technologies at an Islamic High School. The study employed a case study methodology with questionnaires and in-depth interviews as data-gathering techniques. The outcomes of this research focused on the student's learning process of English speaking skills, the obstacles they encounter, and the strategies employed to optimize the use of digital technology in acquiring those skills. The demand for curriculum updates and teacher training may contribute to this trend. Urgent changes are needed in English learning to emphasize broader skill development instead of memorizing vocabulary and grammar. Educational institutions should consider these findings and improve English language instruction accordingly.